MENINGKATKAN HASIL BELAJAR PKN PADA MATERI KEBEBASAN BERORGANISASI MELALUI PENERAPAN TEKNIK KERJA KELOMPOK SISWA KELAS V - Siti Kholijah (JURNAL TEMATIK, 2020)
This study aims to improve student learning outcomes through the application of studentgroup work techniques. This type of research is classroom action research. The subjects of this studywere students of grade 5th SDN 017989 Manis with a total of 22 students. The results of the research atthe time of the initial test before the implementation of the action were with a class average score of67.68 from 22 students. In the first cycle, the material on freedom of organization obtained an averagevalue of 70.22, there was an increase of 3% from the initial value before the repair process was carriedout, namely 67.68. So that after the evaluation as a measure of learning success can be seen with asignificant increase in value, namely the average value to 74.18 in the first cycle, meaning that there isan increase in the percentage of graduation to 100%. In the second cycle, finally what the researchersexpected has been achieved, where the results in Cycle II have reached 100% or all students have beenable to complete learning with an average score of 74.14. From the increase in classical completenessobtained by students, it can be concluded that the use of group work techniques can improve studentlearning outcomes in Civics lessons on freedom of organization in grade 5th SDN 017989 Manis